Exploring Scribling in Padang City Public Sphere - Yendra, Yendra (e-Journal of Linguistics, 2020)
The aim of this study is to explore language in written form that is visible through scribbling in the Padang city public sphere, and focus to describes the linguistic preferences as scribbling form. This study reveal categories of scribbling form which are: (1) form category base on element of language system such as words, phrases, and sentences; (2) form category base on composition of language use such as monolingual, bilingual, and multilingual. Languages compositions in monolingual are Bahasa Indonesia, Minangkabau, English, Arabic, Japanese, Italian, and Spain. Languages composition in bilingual which are, Indonesia + English, Indonesia + Minangkabau, English + Minangkabau, Indonesia + Arabic, English + Arabic, and English + Japanese. Languages composition in bilingual which are Indonesia + Inggris + Minangkabau, Indonesia + English + Arab, Indonesia + English + Latin, and Indonesia + English + Minangkabau + Japanese.